IMPELENTASI PENDIDIKAN INLUSIF DI INDONESIA: ADAPTASI PENDEKATAN HUMANISME - Rahim, Abdul; Taryatman, Taryatman (Universitas Sarjanawiyata Tamansiswa, 2021)
This article aims to describe the implementation of inclusive education through the humanism approach. The method used in writing this article is a literature study. In the context of inclusive education, learning is emphasized on cultivating sympathy, respect, appreciation, and empathy for different socio-cultural backgrounds. Therefore, through inclusive education it is hoped that it can create an environment that is friendly, fun, flexible, can foster self-confidence in students and educators who have special abilities. According to the author, inclusive education can run optimally if it is based on a humanism approach. Because this humanist educational model can instill the principle of recognizing differences in abilities and social constructs. This humanism approach is an approach that positions humans as social creatures to interact with one another and makes it a fun place for students to develop their potential for provision in people's lives. The understanding of humanism that has developed in Western countries today affects the way people perceive the existence of children and their education. This understanding views children as very valuable individuals so that all their rights must be respected and fulfilled. Every child has different potential, development, and needs. These differences must be respected. Through this humanist approach, it is hoped that it can support the implementation of inclusive education.